(untitled) (Bangladesh Journal of Plastic Surgery, 2010)
Introduction: A defect in any part of the body involving extensive soft tissue loss adversely affects the functional ability. With the advent of microvascular free tissue transfer in the reconstruction of large defects, the problem is going to be solved. However, studies are still going on about the different aspects of its success and failure. The present study is one such step to share our early experience. Methods: The study was carried out in the Department of Plastic Surgery, Chittagong Medical College Hospital from August 2009 to April 2010. We reviewed the operative experiences of free tissue transfer on 5 cases. Standard microvascular anastomotic techniques as well as peroperative & postoperative heparinization were maintained in all the cases. Follow up results were evaluated at varying periods following standard protocol. Results: Of the 5 cases reconstructed, 4(80%) had lesions in the maxillofacial region and 1(20%) in the ankle region. In terms of diseases they suffered, 3(60%) had squamous cell carcinoma and 2(40%) sustained mechanical injury. The outcome of treatment demonstrates that 3(60%) cases recovered uneventfully, one developed slight loss of sensation on the left thumb (20%) and another one failed to recover (20%). Conclusion: In this study successful microvascular free tissue transfer was possible in 80% cases. With the increase in experience we can expect increased success rate as well. DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6485 Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.3-8